The application of mike basin model to determine water balance in Cai Phan Rang river basin - Sơn, Hoàng Thanh; Lan, Vũ Thị Thu; Hà, Bùi Hồng (Vietnam Journal of Earth Sciences, 2013)
Located in the southern coastal region of the Centre, Cai Phan Rang river basin (Ninh Thuan Province) characterized by semi-arid ecosystem with high aridity index, hot and sunny weather, lack of water throughout the year.In addition to the impact of climatic conditions, unreasonable use of limited water resource also cause droughts like cropping high water demand plants and employing waste water irrigation methods... In order to overcome and mitigate the effects of droughts, it is necessary to determine the method for efficient use of water through water balance. Authors established a set of MIKE BASIN model parameters that is suitable for Cai Phan Rang river basin - the basin located in the driest region in Vietnam, and applied the model parameters to basin water balance until 2020. With water demand planned by Ninh Thuan province our result shows that the dry areas of Ninh Thuan will continue to face the risk of water shortage for socio-economic development needs.